THE EFFECT OF SERVICE QUALITY ON CUSTOMERS’ SATISFACTION: With Ethnicity as Dummy a Variable (A Study on PT. Bank Rakyat Indonesia (Persero) Tbk. Pasuruan Branch) - Wibowo, Ramadhanif Condro; yo, Sunar (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims at examining the effect of Service Quality and the existing Ethnicity on the Customer Satisfaction at PT. Bank Rakyat Indonesia (Persero) Tbk. Pasuruan Branch. The relationships are observed by conducting the F test and t test with ethnicity as Dummy Variable. The nature of this research itself is as an explanatory research since it is aimed to explain the correlation of some fixed variables. The samples of this research are customers of PT. Bank Rakyat Indonesia (Persero) Tbk. Pasuruan Branch. Sampling technique used is the Quota Sampling. Furthermore, the data obtained through distributed questionnaires are examined by using Validity Test, Reliability Test, and Classical Assumption Tests. The completion of several tests above lead to the data analysis which utilizes Multiple Regression Analysis. Multiple Regression Analysis results show that there is simultaneous effect of Service Quality and Ethnicity on Customer Satisfaction. Partial test proves only Responsiveness, Assurance, Empathy, Tangibles, and Ethnicity have significant effect on Customer Satisfaction while the Reliability does not. In addition, the findings reveal that each ethnic of Javanese, Madurese, and Chinese possess different level of satisfaction. The last test of Dominant Test proves that Empathy has the most influential effect on Customer Satisfaction. Keywords: customer satisfaction, service quality, ethnicity.